Treatment of Multiple Sclerosis With Teriflunomide. Multicenter Study of Real Clinical Practice in the Valencian Community-Spain - Landete, Lamberto; Pérez-Miralles, Francisco; García, Sara; Belenguer, Antonio; Gascón, Francisco; Domínguez, Jose Andres; Carcelén-Gadea, María; Quintanilla-Bordás, Carlos; Navarro, Laura; Gabaldón, Laura; Casanova, Bonaventura (Frontiers in Neurology, 2021)
Introduction: We currently have different treatment alternatives for relapsing-remitting multiple sclerosis -RRMS- within the so-called platform drugs. It would be desirable to know the profile of the ideal patient for each of these drugs. Real clinical practice studies provide us with data on efficacy in the medium and long term, safety beyond clinical trials and can help us to know this patient profile appropriate to each drug. Material and Methods: Observational, multicenter study of real clinical practice in patients with RRMS treated with Teriflunomide in the Valencian Community -SPAIN-, since its approval in Spain. The database created for this study retrospectively collects patients followed prospectively in the consultations. Objectives:to analyze the efficacy and safety of treatment with Teriflunomide in patients with MS-RR, under conditions of real clinical practice and to identify a patient profile responding to treatment. Results: We obtained data from 340 patients who have received at least one dose of Teriflunomide 14 mg. Women 69.4%; mean age 46.4 years; time of progression of MS 11.5 years. Pre-teriflunomide year outbreak rate 0.4; Average EDSS 1.98; Oligoclonal bands of IgG present in the CSF of 66.2% of patients; Oligoclonal bands of IgM present in 46.9%; the mean number of gadolinium+ lesions was 1.07 lesions per patient at the start of treatment. The average number of ttos previously received was 1.04 and 28.53% were naïve. After a follow-up of up to 4 years, a reduction in the annualized and cumulative annualized outbreak rate was observed in the 1st year, in the 2nd year and in the 3rd year, compared to the pre-treatment year. ESDS was stabilized throughout the follow-up. Likewise. There is a reduction in gadolinium+ lesions in the 1st and 2nd year compared to the pre-treatment period. Applying a multiple linear regression model defies a profile of a patient responding to Teriflunomine as a male without oligoclonal bands of IgM in the CSF, a previous EDSS less than 3 and less than 5 years of disease evolution.